The Hunger Games: Aggregatibacter actinomycetemcomitans Exploits Human Neutrophils As an Epinephrine Source for Survival - Ozuna, Hazel; Uriarte, Silvia M.; Demuth, Donald R. (Frontiers in Immunology, 2021)
Aggregatibacter actinomycetemcomitans is a gram-negative facultative anaerobe and an opportunistic oral pathogen, strongly associated with periodontitis and other inflammatory diseases. Periodontitis is a chronic inflammation of the periodontium resulting from the inflammatory response of the host towards the dysbiotic microbial community present at the gingival crevice. Previously, our group identified catecholamines and iron as the signals that activate the QseBC two-component system in A. actinomycetemcomitans, necessary for the organism to acquire iron as a nutrient to survive in the anaerobic environment. However, the source of catecholamines has not been identified. It has been reported that mouse neutrophils can release catecholamines. In periodontitis, large infiltration of neutrophils is found at the subgingival pocket, hence we wanted to test the hypothesis that A. actinomycetemcomitans exploits human neutrophils as a source for catecholamines. In the present study, we showed that human neutrophils synthesize, store and release epinephrine, one of the 3 main types of catecholamines. Human neutrophil challenge with A. actinomycetemcomitans induced exocytosis of neutrophil granules subtypes: secretory vesicles, specific granules, gelatinase granules and azurophilic granules. In addition, by selectively inhibiting granule exocytosis we present the first evidence that epinephrine is stored in azurophilic granules. Using QseC mutants we showed that the periplasmic domain of the QseC sensor kinase is required for the interaction between A. actinomycetemcomitans and epinephrine. Finally, epinephrine-containing supernatants collected from human neutrophils promoted A. actinomycetemcomitans growth and induced the expression of the qseBC operon under anaerobic conditions. Based on our findings we propose that A. actinomycetemcomitans promotes azurophilic granule exocytosis by neutrophils as an epinephrine source to promote bacterial survival.